Impact of perinatal different intrauterine environments on child growth and development in the first six months of life - IVAPSA birth cohort: rationale, design, and methods - Bernardi, Juliana Rombaldi (BioMed Central, 2012)
BACKGROUND: In the last twenty years, retrospective studies have shown that perinatal events may impact the individual health in the medium and long term. However, only a few prospective studies were designed to address this phenomenon. This study aims to describe the design and methods of the Impact of Perinatal Environmental Variations in the First Six Months of Life - the IVAPSA Birth Cohort. METHOD/DESIGN: This is a clinical study and involves the recruitment of a birth cohort from hospitals in Porto Alegre, Rio Grande do Sul, Brazil. Mothers from different clinical backgrounds (hypertensive, diabetics, smokers, having an intrauterine growth restricted child for idiopathic reasons, and controls) will be invited to join the study twenty-four hours after the birth of their child. Data on economic, social, and maternal health care, feeding practices, anthropometric measures, physical activity, and neuropsychological evaluation will be obtained in interviews at postpartum, 7 and 15 days, 1, 3 and 6 months of life. DISCUSSION: To our knowledge, this is the first thematic cohort focused on the effects of intrauterine growth restriction to prospectively enroll mothers from different clinical backgrounds. The IVAPSA Birth Cohort is a promising research platform that can contribute to the knowledge on the relationship between perinatal events and their consequences on the children's early life.